2021
DOI: 10.1155/2021/6648281
|View full text |Cite
|
Sign up to set email alerts
|

Magnetohydrodynamic Fluctuating Free Convection Flow of Second-Grade Fluid Flow in a Porous Medium

Abstract: The article’s objective is to study the magnetohydrodynamic fluctuating free convection flow of incompressible electrically conducting viscoelastic fluid in a porous medium in the presence of a pressure gradient. The flow is between two parallel plates; the lower plate is at rest, while the upper plate moves with a free stream velocity U t … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Some of the work on Jeffrey fluid are of Das [4] and Qasim [5]. Ali et al [6] discussed the magnetohydrodynamic fluctuating free convection flow of incompressible electrically conducting viscoelastic fluid in a porous medium in the presence of a pressure gradient. Shah et al [7] worked on the new semi analytical technique for the solution of fractional Order Navier Stokes equation.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the work on Jeffrey fluid are of Das [4] and Qasim [5]. Ali et al [6] discussed the magnetohydrodynamic fluctuating free convection flow of incompressible electrically conducting viscoelastic fluid in a porous medium in the presence of a pressure gradient. Shah et al [7] worked on the new semi analytical technique for the solution of fractional Order Navier Stokes equation.…”
Section: Introductionmentioning
confidence: 99%
“…It is utilized in chemical industry for filtration, separation, and purification processes which involve the interaction of electric or magnetic field with hydrodynamic boundary layers. Analytical results including porous and MHD terms in second-grade fluid are acquired by Ali et al [10], where there exists the magnetohydrodynamic fluctuating free convection flow of incompressible electrically conducted viscoelastic fluid in a porous medium in the presence of a pressure gradient. Salah [11] analysed the rotationally accelerated fluid and found that variable and constant accelerated MHD flow behave equivalently.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Rajakumar et al 32 examined the Dufour effects on unsteady flow past an impulsively started infinite vertical plate in a porous medium using Walters Bfalse′ $B^{\prime} $ model. Further, Ali et al 33 studied the fluctuating free convective flow of second‐grade fluid in a porous medium.…”
Section: Introductionmentioning
confidence: 99%